MOVING FROM ELDERLY TO BRAND NEW VOCATIONAL EDUCATION BY REMODELING THE EFFECTIVENESS OF DIRECT INSTRUCTION ON INTELLIGENCE AND SOCIAL SKILLS IN SIKATRI MAKE-UP TRAINING - Megasari, Dindy Sinta; Kusnawati, Siti; Winarni, Indah; Hendartini, Rieke (Journal of Vocational and Technical Education (JVTE), 2019)
ABSTRACT The study aims to measure the effectiveness of direct learning on makeup Sikatri material in improving learning outcames. The study was conducted on seventh grade vocational high school students with a total of twenty seven students. The classroom action research technique is applied throughout the information retrieval method. Analysis is distributed on management knowledge and learning outcomes instruments. Control data are going to be calculated by percentage and cross tabulation testing to determine the link between variables. Significance on basic cognitive goals that a procedure for planning and decoding easy strategies of makeup Sikatri by using video. Observation of students' learning activities is applied throughout the cycle and basic skills to broader and authentic reasoning associated with makeup Sikatri are determined through the applying of direct learning. Important variations were obtained with an average increase of 60%. The findings show not only are more students a lot of conscious of using direct instruction but also when asked to design a broader scientific assessment, several students learn how to construct basic information from direct instructions. Additionally, some students were ready to notice their own learning technique after watching a video. These results indicate that the applying of the direct learning through classroom action research is exactly ready to catch up on learning outcomes have been dominated by the discovery approach within the teaching and learning method. Keywords: direct instruction, sikatri makeup, learning outcomes, classroom action research.